Southwestern U.S. Biomass Burning Smoke Hygroscopicity: The Role of Plant Phenology, Chemical Composition, and Combustion Properties. Issue 10 (21st May 2018) - Gomez, S. L.; Carrico, C. M.; Allen, C.; Lam, J.; Dabli, S.; Sullivan, A. P.; Aiken, A. C.; Rahn, T.; Romonosky, D.; Chylek, P.; Sevanto, S.; Dubey, M. K.
Abstract: Biomass burning emissions have substantially increased with continued warming and drying in the southwestern U.S., impacting air quality and atmospheric processes. To better quantify impacts of biomass burning aerosols, an extensive laboratory study of fresh smoke emissions was conducted at Los Alamos National Laboratory. Laboratory burn experiments with selected native and invasive southwestern U.S. fuels were used to elucidate the role of fuel type, chemical composition, and ignition method on the hygroscopicity of smoke. Here we focus on a custom controlled relative humidity (RH) nephelometry system using the direct measurement of aerosol light scattering with two nephelometers—one at dry conditions and one at a controlled high RH (RH ~ 85%). Aerosol hygroscopicity was highly variable with the enhancement in light scattering coefficient in the range of 1.02 <  f (RH = 85%) < 2.1 and corresponding to the kappa parameter ( κ neph ) ranging from ~0 to 0.18. Hygroscopicity is determined primarily by the fuel's inorganic ion content. For example, invasive halophytes with high inorganic salt content exhibit much greater water uptake than native coniferous species with low inorganic content. Combustion temperature and phase, flaming or smoldering, play a secondary role in the water uptake of smoke. High‐temperature ignition methods create flaming conditions that enhance hygroscopicity while lower‐temperature smoldering conditions diminish hygroscopicity. Our results construct an empirical relation between κ neph and the inorganic content of the fuel and smoke to predict water uptake. Key Points: Biomass smoke hygroscopic response is variable, with variability driven by fuel chemical composition and ignition method Coniferous evergreen species are weakly hygroscopic while salt‐tolerant species containing inorganic ions are strongly hygroscopic A framework for smoke hygroscopicity based on lab measurements shows consistent behavior when applied to ambient smoke measurements